2016
DOI: 10.1080/10520295.2016.1220020
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric study of the protective effect of cryotherapy on oral mucositis in cancer patients treated with 5-fluorouracil

Abstract: We investigated cytological changes in oral mucosa smears from patients treated with cryotherapy to determine whether cryotherapy prevented mucositis caused by 5-fluorouracil (5-FU) therapy. Patients with gastrointestinal malignancies were divided into four groups; control patients before 5-FU therapy, patients after 5-FU therapy without cryotherapy, patients with cryotherapy before 5-FU therapy and patients with cryotherapy after 5-FU therapy. Oral mucosa samples from all patients were assessed at the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It was found that the OC decreased pain level of the patients oral mucositis [26], [31], shorter the duration and recovery of severe mucositis [24], [33], reduced the incidence of anorexia [25], and usage of parenteral narcotics [33]. Furthermore, the exfoliative cytology results on the oral mucosal layer showed a decrease in the nuclear and cytoplasmic volume in cells after the OC [32]. However, there were no significant differences between OC and controlled groups in term of the level of toxicity of infectious hematology, analgesic need, TPN [23], the neutrophil rate [30], and length of hospitalization [33].…”
Section: The Effectiveness Of Oc On Other Outcomes In Patients Undergoing Cancer Therapymentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that the OC decreased pain level of the patients oral mucositis [26], [31], shorter the duration and recovery of severe mucositis [24], [33], reduced the incidence of anorexia [25], and usage of parenteral narcotics [33]. Furthermore, the exfoliative cytology results on the oral mucosal layer showed a decrease in the nuclear and cytoplasmic volume in cells after the OC [32]. However, there were no significant differences between OC and controlled groups in term of the level of toxicity of infectious hematology, analgesic need, TPN [23], the neutrophil rate [30], and length of hospitalization [33].…”
Section: The Effectiveness Of Oc On Other Outcomes In Patients Undergoing Cancer Therapymentioning
confidence: 98%
“…The majority of studies applied OC procedures before cancer therapy interventions were carried out. Six studies started giving ice cube 5 min before cancer therapy was started [28], [29], [30], [31], [32], [33]. Another study started 10 min [25] and 30 min before cancer therapy was given [23].…”
Section: Primary Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Oral mucositis usually appears in the second week of RT with fractionated doses of 2 Grays (Gy), and 3‐5 days after bolus or continuous infusions of CH. This side effect causes a loss in the protective function of the mucosal barrier, leading to destruction and breakage of the mucosa, increasing the risk of a local infection due to the colonization of resident microflora, bacteremia, and sepsis . Severe mucositis may be responsible for premature interruption of RT and the reduction in CH dose .…”
Section: Introductionmentioning
confidence: 99%
“…Severe mucositis may be responsible for premature interruption of RT and the reduction in CH dose . Factors that increase OM occurrence are ineffective oral hygiene, nutritional status, alterations in salivary immunoglobulins, and the association of CH and RT …”
Section: Introductionmentioning
confidence: 99%